P.S. I love you [videorecording (DVD)] - LaGravenese, Richard; Swank, Hilary; Butler, Gerard, 1969-; Kudrow, Lisa; Ahern, Cecelia, 1981- (Warner Home Video, 2008)
Holly Kennedy is beautiful, smart and married to the love of her life - a passionate, funny, and impetuous Irishman named Gerry. So when his life is taken by an illness, it takes the life out of Holly. Nobody knows Holly better than Gerry, so it's a good thing he planned ahead. Before he died, Gerry wrote Holly a series of letters that will guide her, not only through her grief, but in rediscovering herself. The first message arrives on Holly's 30th birthday in the form of a cake and a tape recording from Gerry. In the weeks and months that follow, more letters from Gerry are delivered in surprising ways, each sending her on a new adventure and each signing off in the same way - P.S. I Love You. Holly's mother and best friends begin to worry that Gerry's letters are keeping Holly tied to the past, but in fact, each letter is pushing her further into a new future.